Camilla Dickinson [videorecording (DVD)] - Elwes, Cary, 1962-; Mathis, Samantha; Clemens, Adelaide, 1989-; Sulkin, Gregg, 1992-; Moore, Cornelia Duryée, 1959-; Moore, Cornelia Duryée, 1959-; L'Engle, Madeleine (Random Media, 2015)
Film adaptation of Madeleine L'Engle's novel follows daughter of a well-to-do family in 1948 Manhattan. Fifteen-year-old Camilla Dickinson, leads a sheltered life in New York City until her parents' marriage begins to fall apart. When Camilla meets her best friend's rebellious brother Frank she finds a way to escape her troubles. As her relationship with Frank deepens, Camilla discovers a world outside of her own and begins to understand a little of what it means to grow up.